TREND OF COLORS IN LIFE: जीवन में रंगों का रूझान - Vyas, Sadhana (International Journal of Research -GRANTHAALAYAH, 2014)
Many beautiful things affect the life of human beings in the universe, colors have a prominent place among them. Colors contribute uniquely in making the environment attractive. Also, fill the life of a person with happiness, enthusiasm, enthusiasm and consciousness. Being a beautiful world of colors, they have their own importance. The variety of different colors attracts the attention of any person. Colors also show the expression of a person's emotions and emotions. According to Modern Sanctuary en Cyclopedia, "Color is one of the properties of light that the eye sees and different shapes are also formed by light waves." That is, the lack of special kind of stimulation on the retina by the brain is called color. Light is the source of colors. The feeling of color is related to the quality of reflecting or governing the light of each object. सृष्टि में कई सुंदर वस्तुएँ मनुष्य के जीवन को प्रभावित करती हैं, उनमें रंगों का प्रमुख स्थान है। रंग वातावरण को आकर्षक बनाने में अनूठा योगदान देते है। साथ ही व्यक्ति के जीवन को खुषी, उमंग, उत्साह एवं चेतना से भर देते है। रंगों की हसीन दुनिया होने के कारण इनका अपना अलग ही महत्व है। विविध रंगो की छटा किसी भी व्यक्ति का ध्यान बरबसही अपनी ओर खींच लेती है। रंग व्यक्ति के मनोभावों एवं संवेगों की अभिव्यक्ति भी प्रदर्षित करते है। मार्डन संेचुरी एन साइक्लोपीडिया के अनुसार ’’रंग प्रकाष का ही एक गुण है जिन्हें आंखे देखती है और जो विभिन्न आकार भी प्रकाष लहरों से बनते है।’’ अर्थात् मस्तिष्क द्वारा दृष्टिपटल पर विषेष प्रकार की उत्तेजना के अभाव को ही रंग कहते है। प्रकाष रंगों का स्रोत है। रंग की अनुभूति प्रत्येक वस्तु के प्रकाष को परावर्तित अथवा संचालित करने के गुण से संबंधित है।